Two novel mutations in the thyroglobulin gene as cause of congenital hypothyroidism: Identification a cryptic donor splice site in the exon 19 - Targovnik, Hector Manuel (2012)
Thyroglobulin (TG) is a homodimeric glycoprotein synthesized by the thyroid gland. To date, 52 mutations of the TG gene have been identified in humans. The purpose of the present study was to identify and characterize new mutations in the TG gene. We report a French patient with congenital hypothyroidism, mild enlarged thyroid gland and low levels of serum TG. Sequencing of DNA, genotyping, expression of chimeric minigenes as well as bioinformatics analysis were performed. DNA sequencing identified the presence of compound heterozygous mutations in the TG gene: the paternal mutation consists of a c.3788?3789insT or c.3788dupT, whereas the maternal mutation consists of g.IVS19+3_+4delAT. Minigene analysis of the g.IVS19+3_+4delAT mutant showed that the exon 19 is skipped during pre-mRNA splicing or partially included by use of cryptic 50 splice site located to 100 nucleotides downstream of the wild type exon intron junction. The c.3788?3789insT mutation results in a putative truncated protein of 1245 amino acids, whereas g.IVS19+3_4delAT mutation originates two putative truncated proteins of 1330 and 1349 amino acids. In conclusion, we show that the g.IVS19+3_+4delAT mutation promotes the activation of a cryptic donor splice site in the exon 19 of the TG gene. These results open up new perspectives in the knowledge of the mechanism of splicing for the TG pre-mRNA.